KEBIJAKAN PEMERINTAH DAERAH KABUPATEN KUANTAN SINGINGI DALAM MENGATASI TINGKAT KEMISKINAN DI KECAMATAN INUMAN TAHUN 2007-2011 - Wanita, Lesna; ", Isril (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Poverty, welfare, and unemployment is indeed an urgent priority issue to be addressed, both at the national, regional and district / city. Poverty reduction since reforms gained serious attention, because many cases are proving that the spread of poverty pressure will cause a number of counter-productive consequences for development (Ministry of Welfare, 2003). Poverty alleviation is an implementation of the mandate of the 1945 Constitution which has been in jabarkan into various national development agenda. In the Medium Term Development Plan (Plan) for example, the Government has implemented a Poverty Reduction as one of the main development priorities for the period 2009-2014. The document also refers to the National Poverty Reduction Strategy apply consistent achievement of the targets of the MDGs (Millennium Development Goals or MDGs). The purpose of this study was to answer the problems that exist in this study: first, to determine the extent of the district government efforts kuantan singing in overcoming poverty level in the District Inuman Regency Kuantan Singingi Year 2007-2011, the second is to determine what factors which causes the poverty level in the District Inuman Singingi Kuantan District, the third is to know how the impact of government policies on poverty Singingi Kuantan. The findings showed that the policy of the poverty level in the District of Kuantan Singingi is already well underway, but the lack of education that makes a lot of people are unemployed, and added more soil conditions, remote village landslide impede trade network to enter the town. It is therefore expected to Kuantan district government to better control again Singingi poverty level.Key Word : Public policy, Development, Poverty